1999
DOI: 10.1007/s002679900223
|View full text |Cite
|
Sign up to set email alerts
|

PROFILE: Integrated Environmental Management: The Foundations for Successful Practice

Abstract: / Integrated environmental management (IEM) is a holistic and goal-oriented approach to environmental management that addresses interconnections through a strategic approach. Although no models of IEM have emerged, practitioners throughout the world are forging ahead with the concept. The literature indicates that stakeholder collaboration and public involvement are central to operationalizingthis model, because this interaction produces a more integrated approach and generates support for implementation. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 20 publications
1
111
0
10
Order By: Relevance
“…Local residents increasingly perceive themselves as 'stakeholders' in the municipal debate about what is socially desirable and acceptable for their communities; they find that governments, the definitive stakeholders which score high on legitimacy and power, are clearly not doing an effective management job by scoring low on the urgency of an issue (Eythórson, 2003;McDuff, 2001). Numerous studies have confirmed the longing by individuals and groups to have both a voice in, and a closer scrutiny of municipal decisionmaking, especially the environmental policy process (Benest, 1998;Frewer, 1999;Margerum, 1999;Smith, 1998;Abel et al, 2000;Sweeney, 2001). Case studies, where participatory approaches have been applied successfully, are also numerous (Byron et al, 2002;de Loe et al, 2002).…”
Section: Information and Citizens' Participation As Bridgesmentioning
confidence: 99%
“…Local residents increasingly perceive themselves as 'stakeholders' in the municipal debate about what is socially desirable and acceptable for their communities; they find that governments, the definitive stakeholders which score high on legitimacy and power, are clearly not doing an effective management job by scoring low on the urgency of an issue (Eythórson, 2003;McDuff, 2001). Numerous studies have confirmed the longing by individuals and groups to have both a voice in, and a closer scrutiny of municipal decisionmaking, especially the environmental policy process (Benest, 1998;Frewer, 1999;Margerum, 1999;Smith, 1998;Abel et al, 2000;Sweeney, 2001). Case studies, where participatory approaches have been applied successfully, are also numerous (Byron et al, 2002;de Loe et al, 2002).…”
Section: Information and Citizens' Participation As Bridgesmentioning
confidence: 99%
“…The concept of working across boundaries, a regional focus and public consultation have all been long-standing themes in governance (Advisory Commission on Interstate Relations, 1972;Arnstein, 1969;Dworsky and Allee, 1981;Healey, 1997;Rogers and Whetten, 1982). More recently these concepts were updated to reflect the need to examine problems in a more holistic and integrated approach through terminology such as co-management, integrated management, and watershed and ecosystem management (Berkes, 2009;Born and Sonzogni, 1995;Cortner and Moote, 1999;Johnson and Agee, 1988;Loh and Rykiel, 1992;Margerum, 1999). Collaboration is broad and diverse drawing from multiple academic lenses to examine how real-world collaborative arrangements and practice achieve inclusive participation, consensus-based approaches, knowledge sharing, integrated management and supporting networks (Gray, 1989;Innes and Booher, 2009;Margerum, 2011;Robinson et al, 2011).…”
Section: Collaborationmentioning
confidence: 99%
“…Si, formellement, « l'action des OBV ne doit pas se substituer à l'action des usagers ou des acteurs institutionnels » (propos d'un membre de la permanence d'un OBV), ces cas apparaissent donc comme cohérents avec le cadre proposé. Par ailleurs, plusieurs auteurs soulignent l'importance pour les jeunes organismes locaux d'initier rapidement des actions concrètes afin de bâtir la confiance des membres face aux approches participatives (entre autres Barraqué, 1997 ;et Margerum, 1999). En outre, il importe de rappeler qu'en développant des actions sur le terrain de même que l'expertise nécessaire à cette tâche, les OBV développent du même coup des intérêts qui leur sont propres et deviennent eux-mêmes acteurs de l'eau.…”
Section: Des Organismes En Mode « Survie »unclassified